The European Union and Central Asia : challenges and prospects of cooperation - Rakhimov, Mirzokhid; Justus Liebig University Giessen (My University, 2010)
The partnership of CA and the EU concerning political, economical, energy, transport and educational issues should be continued. The partnership will contribute the maintenance and development of peace, stability, cooperation and modernizations in the region. The EU and CA are an important and strong bilateral and multilateral cooperation. This is necessary for economic reforms and for attracting foreign aid and direct investment. Therefore, the EU and CA need to develop a concrete long-range partnership strategy. Regional cooperation in CA and Eurasia will also maintain peace and security in the region. First of all, regional organizations need to concentrate on further regional integration in CA to adequately meet the increasing processes of globalization. It is important to study the experience of the EU and ASEAN and to develop bilateral and multilateral relations with them. A well developed regional transport system in CA is essential for regional prosperity. Regional and international transport networks and substantial trade relations will facilitate foreign investment from foreign countries. CA republics consider the development of alternative regional transport communications as important for the national, regional and international strategy. As a result, a new transport communication connection between Asia and Europe has been developed.The EU and the NATO partnership with CA countries is important for the promotion of stability and security in CA nations. They are also needed to assist the pursuit of sustainable economic development and poverty reduction in the region. At the same time, the stabilization and restoration of Afghanistan s economy are key objectives. Due to different approaches and understandings of the situation in Afghanistan, there are many problems among the different actors including the NATO, the EU, OSCE and other international organizations. In future, the cooperation between CA nations and the EU as well as other international and regional organizations should incorporate the following aspects: Firstly, the EU and CA nations should continue their partnership on alternative transport corridors and pipelines as well as their cooperation in solving a wide range of problems, including ecological ones. Secondly, Afghanistan is an international and regional factor of security and stabilization. Therefore, it is important for the future of CA. Thirdly, the EU, the NATO, and OSCE need to have a regular consultation and joint projects in CA and Afghanistan. Fourthly, international organizations are best to work together with CA republics, Pakistan, Iran, and other neighboring countries. Fifth, the EU, the NATO, and OSCE need to have strong relations and maybe join projects on Afghanistan with Commonwealth Independent States, Shanghai Cooperation Organization, Eurasian Economic Community, and Collective Treaty Security Organizations. Globalization and security challenges require a broader partnership and cooperation. It is necessary to enlarge the Central Asian - EU relations. A future strong partnership would promote stability and economic progress in CA and Europe.
Keywords: ddc:320